PARTISIPASI MASYARAKAT DALAM PROGRAM BANK SAMPAH DI KAMPUNG KELUARGA BERENCANA (KB) KELURAHAN TAMPAN KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Herianti, Gita Melinia; Maemunaty, Titi; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is how high the community's participation in the Waste Bank program in the family planning village (KB) Kelurahan Tampan payung sekaki District pekanbaru city ? and how big is the contribution of community participation to the Waste Bank program based on indicators on the participation variable in family planning villages (KB) Kelurahan Tampan payung sekaki District pekanbaru city. This study aims to determine the level of community participation in the Waste Bank program and to determine the contribution of community participation to the Waste Bank program based on indicators of participation variables. The population of this study is the Customers & Officers of the Family Planning Village Waste Bank (KB) Kelurahan Tampan payung sekaki District pekanbaru city as many as 144 Customers & Waste Bank Officers The sampling technique in this study is the Simple Random Sampling Technique using the slovin formula. The number of samples in this study were 59 people using a questionnaire technique, which amounted to 55 statements of the Participation variable. Data were obtained from 20 respondents for the trial sample and 59 people for the research sample. After the questionnaire was tested, there were 11 invalid statements, and the researcher discarded the invalid statements Based on data analysis from the research results, the demographics of the respondents, namely gender, age, education and livelihood are quite high and based on indicators, namely participation given as closeness of heart is very high, participation skills provided are quite high, participation in ideas, participation labor, property participation is classified as moderate, with the contribution of indicators to the participation variable is classified as low as much as 29.24% and the remaining 70.76%.Key Words: Participation, Community, Waste Bank